A survey of natural mycological and AFB1 contamination in wheat and maize during the 2022 harvesting season in Albania - Topi, Dritan; Risto, Josif; Spahiu, Jeton; Mato, Lorena (Edelweiss Applied Science and Technology, 2024)
Mycotoxins are considered critical contaminants in food and feed, and aflatoxins are the most potent and ubiquitous in maize and wheat. Invasion of toxigenic fungi is manifested in the field and during storage and is directly related to climate and other ecological factors. Inves-tigation of maize and wheat commodity contamination with Aflatoxin B (AFB1) in Albania was conducted during the harvesting seasons of 2022. AFB1 contamination was investigated using the enzyme-linked immunosorbent assay method. Mycological contamination was stud-ied, and fungi from four genera, Aspergillus, Fusarium, Penicillium, and Alternaria, were re-vealed, with maize more frequently contaminated than wheat. Fungi of the Penicillium genus were the most abundant (77.89%), followed by Fusarium (74.73%) and Aspergillus (72.63%). AFB1 contamination is a more critical issue in maize than wheat. The incidence of AFB1 in maize was 88.2%, with a maximum concentration of 69.12 mg/kg; in contrast, AFB1 in wheat was only 4.9%. No samples in wheat had AFB1 concentrations above the EU MRL of 2 µg/kg; in maize, 41.1% of samples exceeded the MRL of 5 µg/kg intended for human con-sumption, and 32.2% exceeded the MRL intended for animal feed. The drastic changes in the administration of arable land from state farms of enormous size to smaller family farms after the '90s have influenced agricultural practices. These findings and climate factors impose that further steps to focus on this issue must be taken by relevant actors to help farmers and in-crease consumer safety.